Decision support for managing an invasive pathogen through efficient clean seed systems: Cassava mosaic disease in Southeast Asia - Andersen Onofre, K.F.; Delaquis, E.; Newby, J.C.; Haan, Stef de; Thuy, C.T.L.; Minato, N.; Legg, James P.; Cuéllar, Wilmer Jose; Briseño, R.I.A.; Garrett, K.A. (Elsevier, 2025)
Context Effective seed systems must distribute high-performing varieties efficiently, and slow or stop the spread of pathogens and pests. Epidemics increasingly threaten crops around the world, endangering the livelihoods of smallholder farmers. Responding to these challenges to food and economic security requires stakeholders to act quickly and decisively during the early stages of pathogen invasions, typically with limited resources. A current threat is the introduction of cassava mosaic virus in Southeast Asia.